Enhancing EFL Students’ Oral Proficiency: The ChatGPT-Assisted Debate Clinic Method - Rahmatullah Syaripuddin (Universitas Muhammadiyah Barru, 2024)
The low level of students’ English oral proficiency was caused by inappropriate learning methods and the lack of a conducive English learning environment created by lecturers. Therefore, this study aims to determine the effectiveness of implementing the ChatGPT-assisted debate clinic approach to enhance students’ oral proficiency in English. This study was conducted using a quantitative approach with a true-experimental design (pretest–posttest control group design). The population involved in this study consisted of third-semester students from the Islamic Religious Education Study Program at STAI DDI Pinrang, Indonesia. The total population was 45 students, and the study sample was 29 students, selected using a total sampling technique. The statistical test results show that the significance values (Asymp. Sig. and Exact Sig.) are very small (0.000), indicating high statistical significance (p < 0.05). This means that there is a significant difference between the post-test data of the two groups. Therefore, teaching English through the ChatGPT-assisted debate clinic method can effectively enhance students’ oral proficiency.